Rendezvous transgastric and percutaneous sinus tract endoscopy (STE) for debridement of necrotic collections with deep retroperitoneal extension: a case series (with video) - Trikudanathan, Guru; Hashmi, Hiba; Dirweesh, Ahmed; Amateau, Stuart; Azeem, Nabeel; Mallery, Shawn; Freeman, Martin L. (Endoscopy International Open, 2020)
Background and study aims Infected necrotic collections extending deep into the retroperitoneum may not be amenable solely to endoscopic necrosectomy. Rendezvous transgastric and percutaneous sinus tract endoscopic necrosectomy was conceived to maximize debridement and obviate the need for open necrosectomy or video-assisted retroperitoneal debridement.Patients and methods Patients who underwent simultaneous rendezvous transgastric and sinus tract endoscopic transluminal necrosectomy at the same session were identified from a prospectively maintained database. Demographic data, clinical outcomes, immediate and late complications were evaluated.Results Among 415 patients with necrotizing pancreatitis, four patients (three males, median age 47 years) underwent this intervention after a median 29.5 days following placement of percutaneous drain. Intra-procedural bleeding following dilation of percutaneous tract required placement of esophageal stent for tamponade. No patients required rescue open necrosectomy or video assisted retroperitoneal debridement. Complete removal of percutaneous drains was accomplished in all patients after a median of 78.5 days.Conclusions Our novel approach is safe and effective and can expand the available armamentarium for management of large necrotic collection with deep retroperitoneal extension.